Bifidobacterium adolescentis protects against necrotizing enterocolitis and upregulates TOLLIP and SIGIRR in premature neonatal rats. Issue 1 (December 2017) - Wu, Wenshen; Wang, Yanli; Zou, Jingjing; Long, Fang; Yan, Huiheng; Zeng, Lijuan; Chen, Yunbin
Abstract Background Necrotizing enterocolitis (NEC) is a serious gastrointestinal disorder that is often seen in premature infants. Probiotics decrease the risk of NEC; however, the mechanism by which probiotics work is not clear. The goal of this study was to evaluate the preventive effect ofBifidobacterium adolescentis in an NEC rat model. Methods Sprague-Dawley neonatal rats were obtained by caesarean section after 20-21 d gestation and randomly divided into the following 3 groups: dam fed (DF), formula fed (FF), and formula + B. adolescentis (FB). Those in the FF and FB groups developed NEC after exposure to asphyxia and cold stress. All rats were sacrificed 72 h after birth and intestinal injury and mRNA expression of TLR4, TOLLIP and SIGIRR were assessed. Results B. adolescentis significantly increased the 72-h survival rate from 56.3% in the FF group to 86.7% in the FB group.B. adolescentis significantly reduced the histological score from a median of 3.0 in the FF group to a median of 1.0 in the FB group, and significantly decreased the rate of NEC-like intestinal injury from 77.8% in the FF group to 23.1% in the FB group. The mRNA expression of TLR4 increased 3.6 fold in the FF group but decreased by 2 fold fromB. adolescentis treatment. mRNA expression of TOLLIP and SIGIRR decreased 4.3 and 3.7 fold, respectively, in the FF group.B. adolescentis significantly increased mRNA expression of TOLLIP and SIGIRR by 3.7 fold and 2.6 fold, respectively. Conclusions This study demonstratedB. adolescentis prevents NEC in preterm neonatal rats and that the mechanism for this action might be associated with the alteration of TLR4, TOLLIP, and SIGIRR expression.